Rancang Bangun Sistem Informasi Manajemen Penjualan Kopi Pada Coffee Shop Konamu Menggunakan Sistem Point Of Sale - ZA, Jhonny; Hadiwinata, Septian Nur (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
The purpose of this research is to develop a coffee sales management information system at the Konamu Coffee Shop using a Point of Sale system to increase efficiency in sales management. The method used in this study is the system development life cycle method, starting from system requirements analysis, system design, system implementation, to system testing. In the system requirements analysis stage, assistance is provided for the problems faced by Konamu Coffee Shop in sales management. Furthermore, a system design is carried out using the Point of Sale system to facilitate the transaction process and sales management. The result of this research is a coffee sales management information system that is integrated with the Point of Sale system. This system can assist Konamu Coffee Shop in managing sales transactions, as well as generating sales and financial reports. With this system, it is hoped that the Konamu Coffee Shop can increase efficiency in managing coffee sales.